Using extended‐duration audio recordings to survey avian species - Amy K. Tegeler; Michael L. Morrison; Joseph M. Szewczak (Wildlife Society Bulletin)
Abstract Point‐count surveys are widely used to infer avian presence and estimate species richness. Advancements in bioacoustic technology enable automated surveys that can supplement human‐based point‐count surveys with expanded temporal and spatial coverage. We surveyed birds in 13 Sierra Nevada and Cascade Range (CA, USA) montane meadows from May to August 2006 using 8 point‐count surveys and automated audio recorders (ARU) to compare species richness between the 2 methods and evaluate the use of ARUs as a monitoring tool. We analyzed species richness using 30 minutes of ARU data per point and 2 point‐count surveys. Automated audio‐recorder data revealed 14 species per meadow (56 species total) while point counts detected 16 species per meadow (67 species total). Automated audio recorders provided >1,100 additional hours of data with personnel effort similar to 2 point‐count surveys. An asymptote in species richness was reached for every meadow using ARU data and 8 of 13 meadows using 2 point‐count surveys. We detected 81 species during all 8 point‐count surveys. We used SonoBird (DNDesign, Arcata, CA) software to search for 24 species detected by point‐count surveys but not in the manually sampled subset of audio files. We detected 22 additional species, bringing the total audio‐file species detections to 85, 4 more than detected by 8 point‐count surveys. We conclude that audio recordings and analysis provide an alternative to avian point‐count surveys or as a supplement to increase their accuracy, particularly over larger temporal and spatial scales, or for species with low detectability. © 2012 The Wildlife Society.